Giant panda distributional and habitat‐use shifts in a changing landscape. Issue 6 (19th June 2018) - Wei, Wei; Swaisgood, Ronald R.; Dai, Qiang; Yang, Zhisong; Yuan, Shibin; Owen, Megan A.; Pilfold, Nicholas W.; Yang, Xuyu; Gu, Xiaodong; Zhou, Hong; Han, Han; Zhang, Jindong; et al.
Abstract: Long‐term data on populations, threats, and habitat‐use changes are fundamentally important for conservation policy and management decisions affecting species, but these data are often in short supply. Here, we analyze survey data from 57, 087 plots collected in approximately three‐fourths of the giant panda's ( Ailuropoda melanoleuca ) distributional range during China's national surveys conducted in 1999–2003 and 2011–2014. Pandas associated preferentially with several ecological factors and avoided areas impacted by human activities, such as roads, livestock, mining, and tourism. Promise is shown by dramatic declines in logging rates, but is counterbalanced with recently emerging threats. Pandas have increasingly utilized secondary forest as these forests recovered under protective measures. Pandas have undergone a distributional shift to higher elevations, despite the elevational stability of their bamboo food source, perhaps in response to a similar upward shift in the distribution of livestock. Our findings showcase robust on‐the‐ground data from one of the largest‐scale survey efforts worldwide for an endangered species and highlight how science and policy have contributed to this remarkable success story, and help frame future management strategies.